Getting Girls into School : Evidence from a Scholarship Program in Cambodia - Filmer, Deon; Schady, Norbert (World Bank, Washington, DC, 2012)
Increasing the schooling attainment of girls is a challenge in much of the developing world. The authors evaluate the impact of a program that gives scholarships to girls making the transition between the last year of primary school and the first year of secondary school in Cambodia. They show that the scholarship program had a large, positive effect on the school enrollment and attendance of girls. Their preferred set of estimates suggests program effects on enrollment and attendance at program schools of 30 to 43 percentage points. Scholarship recipients were also more likely to be enrolled at any scchool (not just program schools) by a margin of 22 to 33 percentage points. The impact of the Japan Fund for Poverty Reduction (JFPR) program appears to have been largest among girls with the lowest socioeconomic status at baseline. The results are robust to a variety of controls for observable differences between scholarship recipients and nonrecipients, to unobserved heterogeneity across girls, and to selective attrition out of the sample.